Evaluation of mangrove restoration effectiveness using remote sensing indices - a case study in Guangxi Shankou Mangrove National Natural Reserve, China - Wang, Yuhang; Wang, Xifei; Khan, Shahbaz; Zhou, Demin; Ke, Yinghai (Frontiers in Marine Science, 2023)
As one of the most productive marine ecosystems in the coastal wetlands, mangrove forests have been severely threatened by intensive human activities. Many countries and regions have carried out mangrove restoration projects. The evaluation of mangrove restoration effectiveness is of great significance for scientific decision-making for restoration engineering and wetland management. In this study, we presented a remote-sensing-based Mangrove Restoration Effectiveness Index (MREI) to evaluate mangrove restoration effectiveness. We took the Guangxi Shankou Mangrove National Natural Reserve (GSMNNR) in China, a UNESCO Biosphere Reserve, as our study area, where four phases of afforestation were implemented during 1990-2022. The MREI was developed based on Landsat-series images by considering the change in mangrove area and the Normalized Difference Vegetation Index (NDVI) from the start year to the end year of each afforestation phase (evaluation period). We further evaluated the Persistence of Restoration Effectiveness (PRE) based on the MREI change trajectory during the whole evaluation period, and the Process-based Restoration Effectiveness Index (PREI) was developed to evaluate the restoration effectiveness at village scale. The results showed that MREI can effectively represent the trajectory of mangrove restoration and showed consistent pattern with high-spatial-resolution imagery. From 1990 to 2022, the mangrove forest area increased from 235.26 ha in 1990 to 873.27 ha in 2022, and 84.59% of the mangrove forest was converted from tidal flats in the reserve. The average value of MREI in the five evaluation phases were 0.48, 0.24, 0.29, 0.17, and 0.72, respectively. The dynamic change of MREI showed that 5.24% of the zones had poor PRE, 44.17% of the zones had excellent PRE. From the perspective of spatial distribution, the Zones with PREI values ranging from high to low were follows: Zone A, E, J, G, C, H, I (D), F, B. Overall, the high value zones of PREI were mainly distributed in the central of the Dandou Sea and the northern part of the Yingluo Bay. The low value zones were distributed in the northwest of the Dandou Sea. We expect the MREI and PREI have great potential to be applied to other regions to evaluate mangrove restoration effectiveness.